(untitled) (The Review of Diabetic Studies, 2023)
Glucagon-like peptide-1 (GLP-1) receptor agonists are a class of injective anti-diabetic drugs that improve glycemic control and many other atherosclerosis-related parameters in patients with type 2 diabetes (T2D). However, the use of this relatively new class of drugs may be associated with certain adverse effects. Concerns have been expressed regarding the effects of these drugs on pancreatic and thyroid tissue, since animal studies and analyses of drug databases indicate an association of GLP-1 receptor agonists with pancreatitis, pancreatic cancer, and thyroid cancer. However, several meta-analyses failed to confirm a cause-effect relation between GLP-1 receptor agonists and the development of these adverse effects. One benefit of GLP-1 receptor agonists is that they do not cause hypoglycemia when combined with metformin or thiazolidinediones, but the dose of concomitant sulphonylurea or insulin may have to be decreased to reduce the risk of hypoglycemic episodes. On the other hand, several case reports have linked the use of these drugs, mainly exenatide, with the occurrence of acute kidney injury, primarily through hemodynamic derangement due to nausea, vomiting, and diarrhea. The most common symptoms associated with the use of GLP-1 receptor agonists are gastrointestinal symptoms, mainly nausea. Other common adverse effects include injection site reactions, headache, and nasopharyngitis, but these effects do not usually result in discontinuation of the drug. Current evidence shows that GLP-1 receptor agonists have no negative effects on the cardiovascular risk of patients with T2D. Thus, GLP-1 receptor agonists appear to have a favorable safety profile, but ongoing trials will further assess their cardiovascular effects. The aim of this review is to analyze critically the available data regarding adverse events of GLP-1 receptor agonists in different anatomic systems published in Pubmed and Scopus. Whenever possible, certain differences between GLP-1 receptor agonists are described. The review also provides the reader with structured data that compare the rates of the most common adverse effects for each of the various GLP-1 receptor agonists.